"Upskirting, " Homosociality, and Craftmanship: A Thematic Analysis of Perpetrator and Viewer Interactions. (February 2022) - Hall, Matthew; Hearn, Jeff; Lewis, Ruth
"Upskirting" is the action or practice of surreptitiously taking photographs or videos up a female's skirt or dress. In the United Kingdom, it is an offense. However, internationally, laws are uneven. Understanding how perpetrators account for their actions becomes an important question. Here, we present the findings of our thematic analysis of posts on the "upskirting" website, The Candid Zone. Our analysis shows that posters and respondents frame this activity as artistic and technical, providing each other with advice and guidance on where and how to get the "best" shots. We conceptualize this form of abuse as homosociality and crafts man ship.